Law Enforcement of Indonesian National Army Soldiers Who Commit Criminal Acts Against Superiors - Bawana, Awang Setyadi; Cahyono, Heru; Aprianti S, Fitri (CV. Rayyan Dwi Bharata, 2025)
This research focuses on the legal enforcement against members of the Indonesian National Army (TNI) who commit the crime of insubordination. Insubordination, defined as defiance or resistance against superiors, is regulated under Articles 105-109 of the Military Criminal Code (KUHPM). This study examines the judicial process in Military Court III-19 Jayapura, specifically related to cases of soldiers disobeying orders from superiors through violent actions. Using normative and empirical legal research methods, this study aims to illustrate how legal mechanisms are applied in military violation cases, particularly in acts of insubordination. The analysis is based on court rulings where the offenders, low-ranking soldiers, were tried and sentenced according to the KUHPM. The results show that while there is a consistent pattern in sentencing, disparities in punishment remain due to various factors such as the severity of the offense and the discretion allowed within the military judicial system. This study recommends clearer guidelines to minimize differences in sentencing and ensure fairness in military justice.